The big walks of the north : including The Pennine Way, the Coast to Coast Walk, Hadrian's Wall Path, the Cleveland Way, the West Highland Way, the Great Glen Way /: including The Pennine Way, the Coast to Coast Walk, Hadrian's Wall Path, the Cleveland Way, the West Highland Way, the Great Glen Way. (©2010) - Unknown
No abstract available